Motivasi Belajar Siswa pada Mata Pelajaran IPS Terpadu: Masa Pandemi Covid-19 (Studi Kasus di MTS Swasta Syafiiyah Besuk Kab. Probolinggo) - Zurohman, Achmad; Taufiq, Ahmad (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2020)
The government's call to stay at home and physical and social distancing must be followed by a change in face-to-face learning to “online” learning (in the network). This study aims so that teachers and students can find out the factors that affect student learning motivation in Integrated Social Studies subjects during the Covid-19 pandemic. In addition, teachers can also find out, modify, and implement several online learning techniques during this pandemic so that student learning motivation remains good. This research method uses qualitative research with a type of case study. Data collection techniques using interviews and documentation. There are several factors that affect student learning motivation in Integrated Social Studies subjects during the Covid-19 pandemic at MTs Private Syafiiyah Besuk Kab. Probolinggo, namely factors from students themselves (internal) and factors from outside (external / teachers). Keywords: student learning motivation, integrated social studies, Covid-19 pandemic